In-situ and real time scanning probe microscopy of organic ultra thin films - Chiodini, Stefano <1985> (Alma Mater Studiorum - Università di Bologna, 2015)
In recent decades, Organic Thin Film Transistors (OTFTs) have attracted lots of interest due to their low cost, large area and flexible properties which have brought them to be considered the building blocks of the future organic electronics. Experimentally, devices based on the same organic material deposited in different ways, i.e. by varying the deposition rate of the molecules, show different electrical performance. As predicted theoretically, this is due to the speed and rate by which charge carriers can be transported by hopping in organic thin films, transport that depends on the molecular arrangement of the molecules. This strongly suggests a correlation between the morphology of the organic semiconductor and the performance of the OTFT and hence motivated us to carry out an in-situ real time SPM study of organic semiconductor growth as an almost unprecedent experiment with the aim to fully describe the morphological evolution of the ultra-thin film and find the relevant morphological parameters affecting the OTFT electrical response. For the case of 6T on silicon oxide, we have shown that the growth mechanism is 2D+3D, with a roughening transition at the third layer and a rapid roughening. Relevant morphological parameters have been extracted by the AFM images. We also developed an original mathematical model to estimate theoretically and more accurately than before, the capacitance of an EFM tip in front of a metallic substrate. Finally, we obtained Ultra High Vacuum (UHV) AFM images of 6T at lying molecules layer both on silicon oxide and on top of 6T islands. Moreover, we performed ex-situ AFM imaging on a bilayer film composed of pentacene (a p-type semiconductor) and C60 (an n-type semiconductor).